TATA KELOLA DAN METODE PROMOSI INDUSTRI PERBANKANDALAM MENINGKATKAN PEMAHAMAN LITERASI KEUANGAN NASABAH - Kesa, Deni Danial (Jurnal Vokasi Indonesia, 2016)
A public company is in need of good corporate governance (GCG) and the right marketing strategy. This will affect the image of a company in attracting potential investors. Promotion methods and conditions of a bank will affect the height of low levels of financial literacy clients. When the portfolio shows that they are at risk of making errors of financial decision makers, customers tend to use the service at relatively liquid bank in consultation with adequate information services. Financial literacy services ease the burden on customers in choosing what the decisions related to the assets of its assets (Hackethal et al, 2012 ; Collins, 2012) by providing theoretical and empirical investigation there are three options in include promotions for acculturation with information services such as the allocation of funding, self-assessment, and the delegation of the banking agencies to decide on what kind of services will be selected.